Kiss me, kill me and other true cases (New York Pocket Star Books, 2004)
An absorbing portrayal of true-crime lovers who kill and the men and women who are their victims.
Keywords: Crime -- Case studies; Criminals -- Case studies; Murder -- Investigation -- United States; Murder -- United States -- Case studies